Highly Shear-Thinning Mucoadhesive Hydrogels for Ophthalmic Applications - Sheikholeslami, Paniz (My University, 2013)
Highly shear-thinning polymers that can easily flow upon the application of shear but form gels at rest have multiple potential applications in the eye. In the front of the eye, a formulation that can easily be administered via a conventional eye dropper but form a gel within the tear film once applied would be beneficial for prolonging drug release at the front of the eye, either alone or as a medium for entrapping nanoparticles or nano-objects loaded with drugs. In the back of the eye, vitreous substitutes that can be administered through a narrow gauge needle (and, ideally, removed via the same) may be beneficial for retinal surgeries.
The overall objective of the proposed research is to chemically modify PVP through grafting strategies to improve its viscometric and mucoadhesive properties while maintaining the beneficial properties, which make it useful in ophthalmic applications.
N-vinylpyrrolidone is copolymerized with N-vinylformamide to produce a functionalized grafting platform P(VP-co-VF), which is then grafted with low concentrations of short hydrophobic grafts to introduce non-Newtonian flow profile to the precursor.
For applications at the back of the eye, the hydrophobic grafted PVP can be injected into the vitreous cavity of the eye in a liquid form to form subsequently a gel-like substance and function as a substitute for the vitreous humour. For application at the front of the eye, the shear thinning properties of hydrophobic-grafted PVP is combined with the mucoadhesive properties of phenylboronic acids (PBA) to improve the bioavailability of the drugs delivered to the front of the eye with eye drops.
Rheological characterization of the solutions has shown the potential to form gel-like materials via hydrophobic associations without sacrificing the facile injectability of the material. Targeted gelation and mucoadhesion properties can be obtained by the synthesis of polymers with desired PBA and hydrophobic graft contents.
Keywords: Shear thinning polymers; hydrophobic-associative polymers; poly vinylpyrrolidone; mucoadhesion; Chemical Engineering; Chemical Engineering